Effect of smoking on Pulse Wave Velocity in different arterial segments (Medical Journal of Indonesia, 2002)
Pulse wave velocity (PWV) was recorded in different arterial segments in 25 male nonsmokers and compared with age and sex matched smokers before and after smoking. Blood pressure (BP), Heart rate (HR) and PWV were comparable between nonsmokers and smokers before smoking. Just after cigarette smoking there was rise in HR, BP and PWV in Aorta to Radial (Ao-Rad), and femoral to Dorsalis Pedis (Fem-Dp) arterial segments, but the PWV was reduced in Aorta to Femoral (Ao-Fem) arterial segment, indicating that both peripheral and central arterial segments show different response to smoking. (Med J Indones 2002; 11: 207-10)Keywords: smoking, pulse wave velocity